PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMODERASI PENGARUH KECERDASAN EMOSIONAL DAN MODAL SOSIAL TERHADAP KINERJA GURU (Studi Kasus Pada Guru SD Di UPP Kecamatan Ampelgading Kabupaten Pemalang) - Eko Hadi Wiryono, 1352020065; Fauzan, Mohammad (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to examine and analyze transformational leadership role in moderating the influence of emotional intelligence and social capital on teacher performance. This study used analysis regrestion method. The study population numbered 271 elementary school teachers. The sample selection procedure was done by using proportional sampling  Rondom using Slovin formula approach with a confidence level of 5% .Sampel UPP 161 elementary school teachers in the District  Ampelgading Pemalang 2015. Transformational leadership as moderating variable is the independent variable that will strengthen or weaken the effect of other independent variables against the dependent variable. The study shows that transformational leadership moderated. the effect of emotional intelligence and social capital on teacher performance.Keywords: Transformational Leadership, Emotional Intelligence Capital Social and Teacher  Performance